Pembuatan Media Interakitf Mengenai Analogi Tubuh Manusia menggunakan Adobe Animate 2022 - Eko Nor Cholis; Riyan Abdul Aziz (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The multimedia development process involves character design, animation, and interactive scenarios using Adobe Animate. This multimedia is designed to be easily accessible to various user levels, taking into consideration the aspects of user experience design.Evaluation results indicate that interactive multimedia created with Adobe Animate is effective in improving the biological concepts understanding of the human body. The interactive interface provides a more engaging learning experience, motivating users to explore further information and enhancing the retention of the concepts taught.This research contributes to the utilization of Adobe Animate as an effective tool for creating educational multimedia. With this approach, it is expected that the teaching of the human body can become more interesting and accessible to various learner groups. Additionally, the findings of this research may pave the way for the development of interactive multimedia based on Adobe Animate in the context of science education.